Scanning tunneling microscopy and spectroscopy of nitrogen doped multi-walled carbon nanotubes produced by the pyrolysis of ferrocene and benzylamine. - Osváth, Z; Koós, A; Grobert, N; Vértesy, Z; Horváth, Z; Biró, L (2009)
In this work, carbon nanotube samples were produced by aerosol chemical vapour deposition from a solution of ferrocene in benzylamine. The multi-walled nanotubes produced by this method were investigated by TEM, SEM/EDS, scanning tunneling microscopy (STM) and tunneling spectroscopy (STS). The dl/dV curves obtained from the STS measurements showed asymmetric density of states (DOS) in nanotubes, with higher DOS above the Fermi energy. These STS measurements and the EDS analysis indicate successful doping with nitrogen originating from the decomposition of benzylamine.